Factor structure of the 6-item Kessler distress scale (K6) and its correlation with the HADS scale in patients with non-psychotic mental disorders - Kustov, G.V.; Isakulyan, E.L.; Gersamia, A.G.; Zinchuk, M.S.; Guekht, A.B. (Èksperimentalʹnaâ psihologiâ, 2025)
Objective. The aim of the present study was to analyze the psychometric properties of the Russian version of the 6-item Kessler Distress Scale (K-6) and to compare it with the Hospital Anxiety and Depression Scale (HADS) in patients with non-psychotic mental disorders. Methods and materials. The psychometric analysis was conducted on a sample of 328 patients with non-psychotic mental disorders, aged 18 to 85 years (M = 54.4 years; SD = 16.7 years). All study participants completed the Russian versions of the K-6 and HADS scales. The validity of the K-6 was assessed using exploratory and confirmatory factor analyses. Results. Analyses indicated a two-factor structure of the scale, including anxiety and depression factors. The internal reliability of the Russian version of the K-6 scale was determined using McDonald's omega coefficient (ω), with values of ω = 0.88. The K-6 scale showed good convergent validity with the HADS scale. Conclusions. The Russian version of the K-6 has significant potential for use in clinical practice and research. Целью настоящего исследования стал анализ психометрических свойств русскоязычной версии шестипунктовой шкалы дистресса Кесслера (К-6) и ее сравнение с Госпитальной шкалой тревоги и депрессии HADS у пациентов с непсихотическими психическими расстройствами. Методы и материалы. Психометрический анализ русскоязычной версии шкалы К-6 был проведен на выборке 328 пациентов с непсихотическими психическими расстройствами в возрасте от 18 до 85 лет (M = 54,4 года; SD = 16,7 года). Все участники исследования заполнили русскоязычные версии К-6 и HADS. Валидность К-6 была оценена с помощью результатов эксплораторного и конфирматорного факторного анализа. Результаты. Установлена двухфакторная структура шкалы, включающая факторы тревоги и депрессии. Внутренняя надежность русскоязычной шкалы К-6 была выявлена с помощью коэффициента омега Макдональда (ω), значения которого составили ω = 0,88. Выявлена хорошая конвергентная валидность шкалы К-6 и HADS. Выводы. K-6 имеет хороший потенциал для использования в клинической практике и в исследовательских целях.